The Role of Islamic Religious Education Teachers in Developing the Pancasila Student Profile Through the Mauizah Method - Rika Fitri; Mulyati Fauzan; Faisal Efendi; Ikhwanuddin Abdul Majid; Adam Adesina Muhammed-Lawal; Musa Zulkifli (FOUNDAE (Foundation of Advanced Education), 2025)
Strengthening the Pancasila Student Profile requires character education that effectively shapes students’ attitudes and behaviors in real contexts. However, Islamic Religious Education at the secondary school level is still frequently dominated by lecture-based methods, formal question-and-answer sessions, and an overreliance on textbooks. Such instructional patterns tend to reduce student engagement and hinder the optimal internalization of Pancasila values. This condition indicates the need for a more humanistic and contextual learning approach that is oriented toward character development. This study not only emphasizes the importance of theory, but also emphasizes practical applications that teachers can implement in the learning process. aiming to investigate how the Role of Islamic Religious Education Teachers in Applying Mauizah Method. Research is qualitative with field research approach using descriptive methods. Primary data was obtained from ten teachers Islamic Education teachers, secondary data from school principals and the curriculum department. The Mauizah method at SMAN 1 Ranah Pesisir reveals a need for innovation in teaching practices, while teachers are essential in conveying Pancasila values, their reliance on monotonous methods, such as lectures and formal question-and-answer sessions, leads to student disengagement. Additionally, the over-dependence on textbooks limits the learning experience. To enhance the effectiveness of the Mauizah method, teachers should diversify their instructional strategies by incorporating interactive techniques and varied resources. This shift is crucial for actively involving students and successfully shaping the Pancasila Student Profile. So that this research is useful for student development in shaping the Pancasila profile. This method needs to be implemented in various schools in order to realize the Pancasila Profile.